Prescription trends at the end of life in a palliative care unit: observational study - Peralta, Tatiana (2022)
Background: Symptomatic control is essential in palliative care, particularly in end‑of‑life, in which the pathophysiological changes that characterize this last phase of life strengthen the need to carry out an early therapeutic review. Hence, we aim to evaluate the prescribing pattern at a palliative care unit at two different time points: on admission and the day of the patient’s death. Methods: Quantitative, analytic, longitudinal, retrospective and observational study. Participants were adult patients who were admitted and died in a palliative care unit, in Portugal. Sociodemographic, clinical and pharmacological data were collected, including frequencies and routes of administration of schedule prescribed drugs and rescue drugs, from the day of admission until the day of death. Results: 115 patients were included with an average age of 70.0 ± 12.9 years old, 53.9 were male, mostly referred by the Hospital Palliative Care Support Teams. The most common pathology was cancer, mainly in advanced stage. On admission, the median scheduled prescription was seven and “as needed” was three drugs. On the day of death, a decrease of prescriptions was observed. Opioids were always the most prescribed drugs. Near death, there was a higher tendency to prescribe butylscopolamine, midazolam, diazepam and levomepromazine. The most frequent route of drug administration was oral on admission and subcutaneous on the day of death. Conclusions: Polypharmacy is a reality in palliative care despite specialist palliative care teams. A reduction of prescribed drugs was verified, essentially due less comorbidity‑oriented drugs. Further studies are required to analyse the importance of Hospital Palliative Care Support Teams.